Customer Delight in Futsal of Pokhara Valley: A Narrative Study From the Customer Perspective - Koirala, Aamod (Journal of Interdisciplinary Studies, 2023)
Futsal is a popular sport in Nepal and futsal centers play an important role in providing opportunities for people to play and enjoy the game. This study explored the factors that contribute to customer delight in futsal centers in Pokhara. A narrative analysis of the stories of futsal participants identified three distinct themes: physical environment, social interaction and surprise and joy. The participants emphasized the importance of a safe and comfortable physical environment, as well as the opportunity to socialize with friends and meet new people. They were also surprised by some of the positive benefits of playing futsal, such as weight loss and improved sleep quality. Finally, they experienced joy from a variety of things, such as winning games, spending time with friends, and being recognized by others. The findings of this study suggest that futsal centers should focus on providing a safe and comfortable physical environment, fostering social interaction, and surprising and delighting customers with unexpected benefits. By doing so, futsal centers can attract and retain customers, build loyalty, and generate positive word-of-mouth.